Timing the laws: Rousseau's theory of development in Corsica. Issue 4 (4th July 2022) - Li, Hansong
Abstract: This paper reinterprets Rousseau's theory of political and economic development through the lens of time. In his governmental plan for Corsica, Rousseau sees an infirm political body about to heal, grow, and prosper under changing conditions, not a static experiment of autarkic agrarianism. Therefore, Rousseau's prescriptions of a hybrid economy, intergenerational office-holding, and future-oriented defence are themselves designed to evolve over time. Rethinking Rousseau's concept of time clarifies long-running debates over the seemingly conflicting images of the philosopher. Neither 'founding' nor 're-founding' Corsica, Rousseau legislates in the interim, aiming for the longevity, not the immortality, of a healthy political economy.